The Impact of Populism on International Law: A Case Study of Nigeria's Role in Regional and Global Governance - Nabiebu, Miebaka; Ekpo, Mokutima Etido; Agube, Ntamy (dialektika kontemporer, 2024)
The rise of populism represents a profound challenge to constitutionalism, democracy, and the rule of law, both within nations and across the global stage. Populist governments increasingly undermine the foundations of international law, multilateralism, and the legitimacy of international legal agreements. This article explores the dangers posed by populism to the international legal order, focusing on its impact on international institutions, non-governmental organizations (NGOs), and the broader framework of global cooperation. Populist regimes often frame international law as a tool for coordination and intervention, eroding its role in safeguarding human rights and fostering collective agreements among nations. By examining these dynamics, this article highlights the growing threat of populism to the international community and proposes strategies to mitigate its effects.